O significado de ser pai e ser mãe de crianças em famílias em vulnerabilidade social - Benatti, Ana Paula (2017)
The concept of parenting has been used to define the functions and roles that parents perform in caring for children and raising them. Therefore, it is not associated with becoming parents, only, but it is been built continuously, through the exercise of their roles and functions (HOUZEL, 2004). In this way, the present study investigated the meaning of motherhood and fatherhood in contexts of social vulnerability, considering that these contexts imply peculiarities to the exercise of parenthood. Six parents and six mothers of children until twelve years-old, who were enrolled in a Centro de Referência de Assistência Social (CRAS) of a municipality in the interior of Rio Grande do Sul participated. The data were collected through a Sociodemographic Questionnaire and a Semistructured Interview and it were analyzed through Content Analysis (BARDIN, 1977). The results showed an overload of tasks related to the maternal role, such as collaboration with the financial support of the family, the accomplishment of the housework, responsibility for the care and education of the children and being helpful to the demands of her husband. Therefore, participants agree that mother should occupy a central place in the family, taking responsibility for tasks such as those above mentioned. This meaning is been related to the feeling of overload experienced by the mothers, since, through it, the mother is individually responsible for performing these tasks, do not allowing that father assumes certain functions that are possible for him to perform. Thus, gender and parental roles remain crystallized. Regarding to fatherhood, it was identified that father is, still, identified as responsible for financial support, being a family authority figure representative, functions traditionally attributed to the fatherly role. This authority is not been seen only about children's education, but also, as emotional support for the mother and as a help to her in moments of making decisions. However, in spite of traditional issues related to the fatherly role, fathers also affirmed participating in other aspects of their children's lives, such as education and teaching values, in their care and protection, and in the affective sphere through games and activities with them. Finally, there was consensus among participants that ideal fatherhood consists in father being present in the family routine and in the children's lives. Furthermore, the present study provided important reflections about the exercise of parenting in contexts of social vulnerability, contributing to the professionals whom work with Brazilian public policies in the care of families, since it has problematized certain peculiarities regarding the meaning of motherhood and fatherhood in these contexts. Thereby, we hope to approximate the conceptions of the professionals, which come from the technical-scientific knowledge, to the conceptions from the popular knowledge, of their users, so that it will be possible to throw a comprehensive look at them and, so, to develop critical and effective actions, that consider the real needs of the population and respect the singularities of the context.